2010
DOI: 10.1002/mame.201000023
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Poly(3‐hydroxybutyrate) Fibers Produced by Melt Spinning

Abstract: Native and nucleated PHB has been melt‐spun and the properties of the resulting fibers have been investigated. Biocompatible nucleating agents such as HAP and THY were compared to BN as a reference material. DSC was used to investigate the non‐isothermal crystallization kinetics as a function of processing temperature and cooling rate. It was found that particularly the choice of process temperature can ensure sufficient primary crystallization of native PHB: heating not higher than 10–15 K above the melting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Melt spinning tests were performed using a self-constructed plunger-piston spinning device: The spinning device, a bi-component spinning system with plunger and piston, was formerly designed and utilized for core-shell fiber spinning. As described elsewhere, compressed air was filled in as core content instead of the second polymer component to fabricate continuous hollow fibers [7]. About 10 g of polymer mixture (granulate material, powder and precipitated material, respectively) was filled in the piston whereas the plunger was already positioned.…”
Section: Melt Spinningmentioning
confidence: 99%
See 2 more Smart Citations
“…Melt spinning tests were performed using a self-constructed plunger-piston spinning device: The spinning device, a bi-component spinning system with plunger and piston, was formerly designed and utilized for core-shell fiber spinning. As described elsewhere, compressed air was filled in as core content instead of the second polymer component to fabricate continuous hollow fibers [7]. About 10 g of polymer mixture (granulate material, powder and precipitated material, respectively) was filled in the piston whereas the plunger was already positioned.…”
Section: Melt Spinningmentioning
confidence: 99%
“…In earlier studies it was shown that PHB can be fabricated to multifilament fibers with textile properties using a highspeed melt spinning and drawing technology and further processed into textile scaffolds and wound healing patches [3][4][5][6]. Recently, we demonstrated that dimensionally stable hollow fibers from PHB can be spun [7]. For instance, latest concepts in neuro-tissue engineering call for biocompatible, biodegradable and biofunctionalized polymers as temporary nerve guidance conduits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinüber et al used a special spinneret to create hollow fibers from poly(3-hydroxybutyrate) (PHB). 37 They showed that meltspinning at low process temperatures without additives led to the formation of well-defined hollow PHB fibers. These hollow fibers can be used to deliver oxygen and nutrients to cells during the culturing period.…”
Section: Meltspinning (Extrusion)mentioning
confidence: 99%
“…This technique has been used to create fibers from various synthetic polymers such as polyethylene terephtalate (PET) (Lu et al, 2005, Sinclair et al, 2010), starch–PCL and starch–poly(lactic acid) (PLA) (Gomes et al, 2008), PLA (Chester and Bornemann, 2008, Ellä et al, 2011, Lu, Simionescu, 2005, Sumanasinghe et al, 2010), and poly(3-hydroxybutyrate) (Chester and Bornemann, 2008, Hinüber et al, 2010). Meltspinning process enables customized fiber constructions including monofilament (Sumanasinghe, Haslauer, 2010), multifilament (Ellä, Annala, 2011), and low denier per filament (DPF) (Sinclair, Webb, 2010) with the ability to create complex cross-sections.…”
Section: Fiber Formation Techniquesmentioning
confidence: 99%